2021
DOI: 10.1007/s00394-021-02576-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrary to ultra-processed foods, the consumption of unprocessed or minimally processed foods is associated with favorable patterns of protein intake, diet quality and lower cardiometabolic risk in French adults (INCA3)

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 58 publications
(67 reference statements)
4
21
1
Order By: Relevance
“…In both children and adults, animal calorie consumption is still above that recommended by the French National Program Nutrition and Health (PNNS), which corresponds to approximately 23-30% of daily calories [40]. For UPF calorie consumption in the last 2015 INCA survey, the level found in adults, i.e., 35%, was close to the data from the French cohort Nutrinet study, i.e., 35.9% UPF calories [68], and that recently found for the same INCA population as in our study, but using the NOVA classification, i.e., 30.6% [69].…”
Section: Adequacy In Meeting the 3v Indexsupporting
confidence: 89%
“…In both children and adults, animal calorie consumption is still above that recommended by the French National Program Nutrition and Health (PNNS), which corresponds to approximately 23-30% of daily calories [40]. For UPF calorie consumption in the last 2015 INCA survey, the level found in adults, i.e., 35%, was close to the data from the French cohort Nutrinet study, i.e., 35.9% UPF calories [68], and that recently found for the same INCA population as in our study, but using the NOVA classification, i.e., 30.6% [69].…”
Section: Adequacy In Meeting the 3v Indexsupporting
confidence: 89%
“…Several prospective studies have found that consumption of plant foods such as legumes, whole grains, and nuts is associated with lower cancer rates, cardiovascular disease risk, and all-cause mortality, whereas red and processed meat is generally associated with an elevated risk 62 , 63 , particularly when consumed as part of Standard American/Western diets 64 66 . It must be noted that in the context of healthful dietary patterns, plant-based (vegan/vegetarian) and omnivorous diets may be equally associated with lower chronic metabolic disease risk and/or mortality 67 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, in higher UPFs consumers, intake of plant-based protein was higher because of higher intake of bread and refined grains. Higher consumption of UPFs was related to lower protein intakes as increased intake of miscellaneous foods groups low in protein like sweetened drinks, pastries, or confectionary [ 58 ]. Pervious studies have reported that diluation of protein in diet by either fat or carbohydrate will result in excessive food intake to reach the protein intake target, as a known phonomenon named ‘protein leverage’.…”
Section: Discussionmentioning
confidence: 99%